Navigating “Second-Class” Citizenship: Minority Perceptions of the “Gospel City” Regulation in Manokwari - Dani Muhtada; Dwi Wisnu Kurniawan; Rayyan Alkhair; Javandalas Nanda Yasser Fatahillah; Andi Gazly Satrya Amal (Lex Scientia Law Review, 2026)
This article examines the implications of Manokwari Regency Regulation No. 3 of 2018 concerning the Arrangement of Manokwari as a Gospel City (Penataan Manokwari sebagai Daerah Injil) for the civil rights of religious minorities and explores how religion-related regional regulations can be formulated to strengthen national integration. Drawing on the theories of symbolic legislation, legal pluralism, and accommodative leadership, the study employs a qualitative descriptive-analytical approach based on in-depth interviews with Muslim, Hindu, and Buddhist religious leaders in Manokwari. The findings reveal a paradoxical relationship between symbolic law and social reality. At the symbolic level, many minority respondents perceive the regulation as privileging a particular religious identity and raising concerns regarding equality, recognition, and religious freedom. However, its practical impact on the everyday lives of minority communities remains limited. This is largely because the most restrictive provisions contained in earlier drafts were removed, no implementing regulations were subsequently issued, and the regulation's effects have been moderated by local mechanisms of coexistence. The study highlights the importance of the Satu Tungku Tiga Batu philosophy, customary authority, and accommodative local leadership in sustaining interreligious harmony and mitigating the potential exclusionary effects of formal law. The article argues that the Manokwari case illustrates the limits of symbolic legislation in shaping social relations within a plural society. It concludes that the protection of minority rights and the strengthening of national integration are more likely to be achieved through inclusive, non-discriminatory, and substantively oriented regulations that accommodate legal and cultural diversity rather than through the formal affirmation of a single religious identity.